2014
DOI: 10.1103/physrevlett.112.143601
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Control of Molecular Gas Hydrodynamics

Abstract: We demonstrate that strong impulsive gas heating or heating suppression at standard temperature and pressure can occur from coherent rotational excitation or deexcitation of molecular gases using a sequence of nonionizing laser pulses. For the case of excitation, subsequent collisional decoherence of the ensemble leads to gas heating significantly exceeding that from plasma absorption under the same laser focusing conditions. In both cases, the macroscopic hydrodynamics of the gas can be finely controlled with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…Intense ultrashort laser pulses can deposit energy in a transparent gas medium either by ionizing [1,2] or spinning up [3,4] its molecular constituents. Heating of the gas is followed by the formation of an acoustic wave [5][6][7][8] which leaves behind a long-lived low-density depression channel [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intense ultrashort laser pulses can deposit energy in a transparent gas medium either by ionizing [1,2] or spinning up [3,4] its molecular constituents. Heating of the gas is followed by the formation of an acoustic wave [5][6][7][8] which leaves behind a long-lived low-density depression channel [9].…”
Section: Introductionmentioning
confidence: 99%
“…Heating of the gas is followed by the formation of an acoustic wave [5][6][7][8] which leaves behind a long-lived low-density depression channel [9]. Laser-induced sound emission is key to photoacoustic spectroscopy [10][11][12], whereas laser control of the gas density proved valuable for generating [13,14] and even controlling [4] wave-guiding channels in ambient air. Because ionization-free delivery of energy by means of rotational excitation does not inhibit coherent light propagation through the heated gas, it has the potential of producing longer wave guides, e.g., if executed inside ionization-free filaments [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of laserinduced pressure waves in dense media [22], as well as numerical simulations of hydrodynamic expansion [7], the sound wave amplitude is expected to scale linearly with the amount of laser energy deposited in the sample. In the case of an impulsive rotational excitation, most of the energy is transferred via a single two-photon Raman transition, suggesting a quadratic dependence on the pulse energy [4], which has been recently verified experimentally [6,11]. In contrast, an adiabatic excitation by the centrifuge involves multiple transitions up RAMAN: One of the spectra from Sep26a sound data.…”
mentioning
confidence: 99%
“…Nonlinear change of refractive index gives rise to filamentation (recent reviews of this broad topic can be found in [1,2]), whereas spatially localized heating results in the formation of acoustic waves [3][4][5][6][7][8] and long-lived gas density perturbations [9][10][11]. Photo-acoustic vibrational Raman spectroscopy has been successfully utilized for chemical detection and trace analysis [12,13].…”
mentioning
confidence: 99%
“…Magnetic effects could further broaden the controllability provided by tunable rotational excitation, including control of molecular collisions [12,13] and scattering of molecules at gas-solid interfaces [14], molecular trajectories [15] and formation of gas vortices [16], optical [5,17] and acoustic [19,20] properties of a gas of rotating molecules.…”
mentioning
confidence: 99%